2017
DOI: 10.5901/mjss.2017.v8n1p299
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Barriers to Accessing Maternal Healthcare Systems in Developing Countries: A Case of Sokoto-Northern Nigeria

Abstract: The government and other policy makers continue struggles to achieve maximum access of modern healthcare by the women in developing countries. To assist actualising such goal this study intends to examine the influence of distance to facility, time taken for travel and means of transportation (DTTf)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Women are prohibited from leaving their homes for health care in the most countries of SSA [ 17 ]. A study in rural SSA countries showed that women living in communities are not expected to visit health care facilities, which reduces the Service utilization in the health care system [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women are prohibited from leaving their homes for health care in the most countries of SSA [ 17 ]. A study in rural SSA countries showed that women living in communities are not expected to visit health care facilities, which reduces the Service utilization in the health care system [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study in Zambia by Sialubanje et al (2015), women's independence was found to be part of the factors that caused low patronage of the services of skilled healthcare workers in the maternal centres. Husband dominance significantly limits women's freedom to seek healthcare services (Shamaki, Yew, & Dahiru 2017). However, when women are not supported by their husbands, they can patronise the TBAs, whose services are cheap and free, depending on the situation.…”
Section: Husband Supremacymentioning
confidence: 99%
“…The mode of travel and the status of transportation infrastructure are critically important factors that influence the amount of time required for access [82,86,102,[107][108][109]. Many poor rural families do not own vehicles, cannot afford to hire vehicles [110] and are not within reach of public transportation systems that typically only follow patterns of commerce [90]. Thus, the available modes of transportation are often less advanced, and people are left to rely upon low-technology and high-effort options, compounding the burdensome and time-consuming nature of their journeys [84,86,101,[110][111][112].…”
Section: Health Impactmentioning
confidence: 99%
“…Many poor rural families do not own vehicles, cannot afford to hire vehicles [110] and are not within reach of public transportation systems that typically only follow patterns of commerce [90]. Thus, the available modes of transportation are often less advanced, and people are left to rely upon low-technology and high-effort options, compounding the burdensome and time-consuming nature of their journeys [84,86,101,[110][111][112]. Additionally, an ill or injured person, or an adult traveling with children, will have decreased ability to travel via these means, and doing so can be slow, dangerous, or life-threatening [81,82,84].…”
Section: Health Impactmentioning
confidence: 99%
See 1 more Smart Citation